Sentencing Vulnerability: An Empirical Study Into the Role of Personal Characteristics and the Foreseeable Experience of Confinement at the Sentencing of Older Adults - Iftene, Adelina; Hearns, Allison (Ottawa Law Review / Revue de droit d’Ottawa, 2024)
This article presents and analyzes findings from a qualitative and quantitative review of reported Nova Scotia sentencing decisions (2013–2020) of aging individuals. The goal is twofold. First, by investigating the judicial discourse around personal characteristics at sentencing aging individuals, we specifically seek to understand where aging, and characteristics that interplay with aging, fit into current sentencing practices and the potential benefits and challenges of considering these factors. Secondly, and more generally, through the case study of older offenders, this article seeks to contribute to the largely theoretical scholarship that has engaged with the need for a methodical inclusion of a broader range of personal characteristics and experiences in sentencing.The review highlights a number of things. First, it shows that implementing a “characteristics and experience sensitive sentencing” (CESS) framework is possible because it is already occasionally used. Second, it shows that ignoring characteristics and experiences of offenders is not feasible; even if it was desirable to do so, these cannot always be ignored and they currently make their way into sentencing decisions in inconsistent ways, based on very different approaches, which, in turn, result in very different outcomes. Adopting a coherent approach to the use of personal characteristics and experiences is now a matter of bringing consistency in sentencing and a matter of promoting substantive over formal equality. Third, the study shows that sentencing decisions are filled with misconceptions about imprisonment and its impact on those sentenced. Some of the beliefs relied upon are not evidence-based, and yet they sometimes ground the sentencing decisions rendered. Implementing a CESS framework would require directly confronting and addressing these misconceptions. Fourth, the study highlights both some of the barriers to the implementation of a CESS framework and some possible solutions that would help overcome these barriers.